Cardiovascular outcomes of metformin use in patients with type 2 diabetes and chronic obstructive pulmonary disease - Yen, Fu-Shun; Wei, James Cheng-Chung; Chiu, Lu-Ting; Hsu, Chih-Cheng; Hwu, Chii-Min (Frontiers in Pharmacology, 2022)
Aims: To know whether metformin use has different impact on cardiovascular risks in patients with type 2 diabetes mellitus (T2DM) and chronic obstructive pulmonary disease (COPD) as compared with metformin no-use. Methods: This study employed a retrospective cohort study design. We recruited 55 224 propensity score–matched metformin users and nonusers from Taiwan’s National Health Insurance Research Database between January 1, 2000, and December 31, 2017. Cox proportional-hazards models with robust standard error estimates were used to compare the risks of cardiovascular outcomes. Results: The mean follow-up time of metformin users and nonusers was 11.04 (5.46) and 12.30 (4.85) years, respectively. Compared with the nonuse of metformin, the adjusted hazard ratios (95% CI) of metformin use for composited cardiovascular events, stroke, coronary artery disease, and heart failure were 0.51 (0.48-0.53), 0.62 (0.59-0.64), 0.48 (0.46-0.50), and 0.61 (0.57-0.65), respectively. The longer cumulative duration of metformin use had even lower adjusted hazard ratios compared with metformin nonuse. Conclusions: In patients with coexisting T2DM and COPD, metformin use was associated with significantly lower risks of CVD; moreover, longer duration of metformin use was associated with a lower risk of CVD. A well-designed prospective study is required to verify the results.